Examining the influence of perceived organizational support towards job-hopping behaviour: a case of casual dining restaurant employees’ in Klang Valley area, Malaysia - Ghazali, Hazrina; Jules, Nathalie Joan; Othman, Mohhidin (Global Academic Excellence, 2018)
Food and beverage industries are playing a big role in offering a wide range of job vacancies for job seekers. With many job vacancies and opportunities available, people are moving from one job to another. This behaviour called job hopping. Theoretically, employees with higher perceive organization support tends to have lower intention to quit and job hop to another company to work with. This has caused organizations restless in retaining employees especially skilled and valuable were not an easy task. It was uncertain either these employees have a low level of their perceived organization support or job hop for no apparent reason. Thus, the main objective of this study conducted was to determine employee’s perceived organization support mediated with affective commitment towards their job-hopping behaviour. Methodologically, main primary data used in this study were quantitative data survey, which was distributed to employees of casual dining restaurants in Klang Valley area, Malaysia. Criteria for selection of respondents were strictly only Malaysian and who had worked at least a year throughout their working career. Total of 612 questionnaires was usable for data analysis. After the screening of eligible respondents, data were analysed using Software Package Statistical Analysis (SPSS) version 21 and PROCESS MACRO plugin for regression analysis together with bootstrapping method to determine mediation effect. The result indicated perceived organization support predicts job-hopping behaviour with negative significant relationship (Beta = -.087, p-value < .05). When perceived organization support held constant with mediator affective commitment predicting job hopping, it was directed that mediation occur in the relationship and is significant. Employees of casual dining restaurants with a higher level of perceived organization support tend to have a higher affective commitment towards their organization and a lesser tendency to job hop. With peer and supervisor support available for one, one will feel being part of the organization. Hence, Volume: 3 Issues: 12 [June, 2018] pp. 101 - 108] International Journal of Accounting, Finance and Business eISSN: 0128-1844 Journal website: www.ijafb.com102 employers may provide moral support for their respective employees in need apart from given that basic well-being in place while motivate and retain them.